2018
DOI: 10.24193/ojmne.2018.27.02
|View full text |Cite
|
Sign up to set email alerts
|

Does Tax Competition for Capital Define Entrepreneurship Trends in Eastern Europe?

Abstract: The article deals with the analysis of relationships between tax competition and entrepreneurship development in Eastern European and Baltic countries during 2006-2017. Incomplete nature of tax systems reforming in these countries forms preconditions for their participation in crosscountry tax competition in investment flows reallocation. The main instrument of the tax competition includes tax rates, which are defined by convergence tendencies in the studied countries. Other factors of the research are tax bur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 2 publications
1
25
0
Order By: Relevance
“…− A sudden increase in unemployment in the years 1990-1995 forcing entire families to take on new challenges in the form of starting a business. − Very high cost of raising capital associated with high inflation and fiscal policy during the economic reforms (1990)(1991)(1992)(1993)(1994)(1995)(1996)(1997)(1998)(1999) favouring family accumulation and allocation of capital needed to start a new business (McMilian & Woodruff, 2003;Bilan at al., 2018). − The key position of the family in studies of the hierarchy of social values in Poland that has been sustained over many recent decades (Nowak, 1981).…”
Section: Characteristics Of Family Entrepreneurship In Polandmentioning
confidence: 99%
“…− A sudden increase in unemployment in the years 1990-1995 forcing entire families to take on new challenges in the form of starting a business. − Very high cost of raising capital associated with high inflation and fiscal policy during the economic reforms (1990)(1991)(1992)(1993)(1994)(1995)(1996)(1997)(1998)(1999) favouring family accumulation and allocation of capital needed to start a new business (McMilian & Woodruff, 2003;Bilan at al., 2018). − The key position of the family in studies of the hierarchy of social values in Poland that has been sustained over many recent decades (Nowak, 1981).…”
Section: Characteristics Of Family Entrepreneurship In Polandmentioning
confidence: 99%
“…The Czech Republic is the traditional destination of Slovaks due to their common historical, linguistic, cultural and geographic proximity and favourable regulatory policies among the countries. The number of Slovaks working in Hungary is also estimated to be around 20,000, with more than 13,000 workers commuting to work from Slovakia to Hungary daily (Bolečeková et al, 2018;Šprocha et al, 2018;Vasylieva and Samusevych, 2018). OECD estimates indicated that between 2004 and 2010, on average about 10,000 Czech nationals returned home compared to 13,000 Slovaks and 22,000 Hungarians (Zaiceva and Zimmermann, 2016).…”
Section: Overview Of the Recent Labour Migrations From Czech Republicmentioning
confidence: 99%
“…Harold (2018) proves the relationship between amounts of foreign trade and economic growth. Bilan et al (2018) include inflation and direct foreign investment to the control variables block in the study. The informational base of the research includes official data, represented on sites of OCD and World Bank group.…”
Section: Marketing and Management Of Innovations 2018 Issuementioning
confidence: 99%